Increasing Cyberbullying Awareness through Cognitive Behavior-Based Spiritual Counseling: Systematic Review - Putra, Febri Wandha; Zahri, Triave Nuzila; Fadli, Rima Pratiwi; Maharani, Ade; Abdillah, Maulana Hamid (Universitas Negeri Padang, 2024)
One of the negative impacts is the increasing phenomenon of cyberbullying today. Cyberbullying cases occur in almost all countries around the world. Individuals who engage in cyberbullying tend to have low self-awareness. This study aims to identify the impact of cognitive behavioural spiritual counselling in increasing awareness of cyberbullying. A systematic review was conducted over the past five years using the keywords “cyberbullying, cyberbullying awareness, spiritual counselling, cognitive behaviour” and the population, intervention, comparison, outcomes, and study design (PICOS) in the Scopus database (187 articles), Willey (69 articles), and Science Direct (70 articles) published in the past five years using the keywords “cyberbullying, cyberbullying awareness, spiritual counselling, cognitive behaviour”. The selected articles were those using quantitative and longitudinal research methods published between 2019 and 2024, where the study participants were adolescents who had either engaged in or witnessed cyberbullying. A total of 30 articles met the inclusion criteria for this review. Based on the results of the article review, it was found that awareness of cyberbullying can be increased through cognitive behaviour-based spiritual counselling services. Cognitive behaviour-based spiritual counselling services aim to help individuals identify various physical, emotional, and spiritual responses, enabling clients to redefine themselves and enhance their understanding and rational beliefs by eliminating irrational thoughts.